A recurrent network in the lateral amygdala: a mechanism for coincidence detection - Johnson, Luke R.; Hou, Mian; Ponce-Alvarez, Adrian; Gribelyuk, Leo; Alphs, Hannah; Albert Jr, Ladislau; Brown, Bruce L.; LeDoux, Joseph; Doyere, Valerie (Frontiers in Neural Circuits, 2008)
Synaptic changes at sensory inputs to the dorsal nucleus of the lateral amygdala (LAd) play a key role in the acquisition and storage of associative fear memory. However, neither the temporal nor spatial architecture of the LAd network response to sensory signals is understood. We developed a method for the elucidation of network behavior. Using this approach, temporally patterned polysynaptic recurrent network responses were found in LAd (intra-LA), both in vitro and in vivo, in response to activation of thalamic sensory afferents. Potentiation of thalamic afferents resulted in a depression of intra-LA synaptic activity, indicating a homeostatic response to changes in synaptic strength within the LAd network. Additionally; the latencies of thalamic afferent triggered recurrent network activity within the LAd overlap with known later occurring cortical afferent latencies. Thus, this recurrent network may facilitate temporal coincidence of sensory afferents within LAd during associative learning.